Decoding Gen Z Retention: The Interplay Between Authentic Leadership, Work-Life Balance, and Digital Nomadism Tendencies - Casimiro Soares; Arlindo do Céu Fatima (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2026)
This study examines the interplay between authentic leadership, work-life balance, and digital nomadism tendencies in influencing Generation Z employee retention within small and medium enterprises (SMEs) in Dili, Timor-Leste. Employing a quantitative associative research design, data were collected from 385 Gen Z employees using purposive sampling. The analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS to test both direct and interaction effects. The results reveal that authentic leadership and work-life balance have positive and significant effects on employee retention, indicating that supportive leadership practices and balanced work conditions enhance employees’ intention to stay. In contrast, digital nomadism tendencies show a significant negative effect, suggesting that a stronger preference for flexible, location-independent work reduces retention. Furthermore, digital nomadism is found to weaken the positive influence of authentic leadership and work-life balance on retention, highlighting its moderating role. The study contributes theoretically by integrating organizational and individual lifestyle factors into a comprehensive retention model, particularly within the underexplored SME context in a developing country. Practically, the findings suggest that SMEs must adopt adaptive human resource strategies by combining strong leadership, employee well-being, and flexible work arrangements to retain Gen Z employees. The study is limited by its cross-sectional design and geographic focus; therefore, future research is recommended to explore longitudinal data and broader contexts. Overall, this research provides valuable insights into managing the evolving expectations of the Gen Z workforce in the digital era.